El estudio de Medio Oriente en la disciplina de relaciones internacionales en México - Tawil Kuri, Marta (El Colegio de México A.C., 2016)
The present work is mostly based on BA, Masters degree and PhD theses on Middle Eastern issues and countries that have been written by students of international relations since 1980 in four Mexican universities. Predominant topics as well as methodological and theoretical tools are identified, which are then linked to the question of knowing how the growing interest in the Middle East among Mexican internationalists, and their efforts in this field, are effectively reflected in both the publication of articles and books in Mexico, and in the policy relevance and public engagement of scholars. What has been detected so far gives an encouraging and at the same time disconcerting picture, related to research and documentation networks, financial resources, and the priorities set out by Mexico’s national neoliberalist identity and structural positionality.